A new species and the first record of the genus Micrapemon Edwards (Diptera: Keroplatidae) from Mexico - Huerta, Heron (Zootaxa, 2019)
The first record of the genus Micrapemon Edwards from Mexico is presented, with the description and illustration of a new species, Micrapemon maya spec. nov., based on adult males collected with Malaise traps from Yucatan (natural reserves of Ria Celestun and Ria Lagartos). The new species from Mexico is compared with the two previously known species from the Neotropical region, Micrapemon majusculum (Edwards) and Micrapemon parvum (Williston). A key is included to the species of the genus.